Manajemen Penanganan dan Upaya Pencegahan Insiden Anemia dalam Kehamilan - Fitriani, Novi; Hidayatullah, Muhammad Dwi; Vera Hayati, Thursina; Frisilia Dewi, Sri Yuliani; Syafhira, Adinda; Maryanto, Hendri; Hasyim, Hamzah; Usman, Najmah (Jurnal Ilmiah Administrasi Publik, 2023)
Anemia during pregnancy is a health problem that threatens both mother and fetus. A systematic review was conducted of relevant studies to determine the factors that cause pregnancy anemia and how to prevent it. The method used is a literature study using flowchart prisms from various sources. The results showed that maternal age, number of parities, nutritional status, rural residence and economic status, diet during pregnancy, and adherence to iron tablet use contributed to pregnancy anemia. To prevent anemia in pregnancy, women aged <20 years and >35 years or who have SEZ can postpone their pregnancy. Prevention can also be done through health services in the form of health centers that have good health management to realize the health of pregnant women by organizing and planning health services.